Blend Hybrid Solid Electrolytes Based on LiTFSI Doped Silica-Polyethylene Oxide for Lithium-Ion Batteries - Mosa, Jadra (Membranes (Basel), 2019)
Organic/inorganic hybrid membranes that are based on GTT (GPTMS-TMES-TPTE) system while using 3-Glycidoxypropyl-trimethoxysilane (GPTMS), Trimethyletoxisilane (TMES), and Trimethylolpropane triglycidyl ether (TPTE) as precursors have been obtained while using a combination of organic polymerization and sol-gel synthesis to be used as electrolytes in Li-ion batteries. Self-supported materials and thin-films solid hybrid electrolytes that were doped with Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were prepared. The hybrid network is based on highly cross-linked structures with high ionic conductivity. The dependency of the crosslinked hybrid structure and polymerization grade on ionic conductivity is studied. Ionic conductivity depends on triepoxy precursor (TPTE) and the accessibility of Li ions in the organic network, reaching a maximum ionic conductivity of 1.3 × 10(−4) and 1.4 × 10(−3) S cm(−1) at room temperature and 60 °C, respectively. A wide electrochemical stability window in the range of 1.5–5 V facilitates its use as solid electrolytes in next-generation of Li-ion batteries.